2017
DOI: 10.14814/phy2.13062
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time imaging of sodium glucose transporter (SGLT1) trafficking and activity in single cells

Abstract: The processes controlling targeting of glucose transporters to apical and basolateral membranes of polarized cells are complex and not‐well understood. We have engineered SGLT1 and GLUT4 constructs linked to fluorescent proteins to highlight the differences in transporter expression and trafficking, in real time, in different cell types. Activity was assessed in parallel using a FRET glucose sensor. In COS cells and HEK cells, SGLT1 was distributed between the plasma membrane and intracellular compartments, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
0
15
1
Order By: Relevance
“…Another study showed that CAV1 increases the expression, activity, and transport of SGLT1 to the cell membrane in Xenopus oocytes [206]. However, a new study showed that SGLT1 internalization is lipid raft-dependent but CAV1-independent in HEK and COS cells [207]. Though CAV1 tends to improve glycemic control and associated complications via its interaction with various drug targets and downstream signaling molecules, its potential use as an antidiabetic drug requires further in-depth studies.…”
mentioning
confidence: 99%
“…Another study showed that CAV1 increases the expression, activity, and transport of SGLT1 to the cell membrane in Xenopus oocytes [206]. However, a new study showed that SGLT1 internalization is lipid raft-dependent but CAV1-independent in HEK and COS cells [207]. Though CAV1 tends to improve glycemic control and associated complications via its interaction with various drug targets and downstream signaling molecules, its potential use as an antidiabetic drug requires further in-depth studies.…”
mentioning
confidence: 99%
“…Glucose is transported from the small intestinal lumen, through the epithelium into the underlying serosa. The sodium‐dependent glucose transporter (SGLT1) is most abundant in the small intestine epithelium and is believed to allow glucose and galactose to cross the luminal epithelium into the small intestinal absorptive cells . SGLT1 undergoes a succession of conformational changes in response to the binding of sodium ions and glucose .…”
Section: Absorption Of Glucose In the Gastrointestinal Tractmentioning
confidence: 99%
“…The sodium‐dependent glucose transporter (SGLT1) is most abundant in the small intestine epithelium and is believed to allow glucose and galactose to cross the luminal epithelium into the small intestinal absorptive cells . SGLT1 undergoes a succession of conformational changes in response to the binding of sodium ions and glucose . It appears that each glucose molecule requires the binding of two sodium ions .…”
Section: Absorption Of Glucose In the Gastrointestinal Tractmentioning
confidence: 99%
“…The incorporation of SGLT1 in the plasma membrane is balanced by the endocytosis of SGLT1 from the plasma membrane. SGLT1 has been documented to be endocytosed from the plasma membrane of cultured cells in a clathrin-and caveolin-independent manner (Ghezzi et al, 2017). Following endocytosis, SGLT1 could be targeted to the lysosomes for proteolysis or recycled back to the plasma membrane (Ghezzi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…SGLT1 has been documented to be endocytosed from the plasma membrane of cultured cells in a clathrin-and caveolin-independent manner (Ghezzi et al, 2017). Following endocytosis, SGLT1 could be targeted to the lysosomes for proteolysis or recycled back to the plasma membrane (Ghezzi et al, 2017). While these results have provided evidence supporting that endocytosis and the downstream lysosomal degradation and recycling are important intracellular trafficking pathways that regulate the availability of SGLT1 in the plasma membrane, they were obtained from in vitro work that utilized cultured cells which are not models for human enterocytes.…”
Section: Introductionmentioning
confidence: 99%